Engaging Preservice Teachers in Collaborative Inquiry Projects During Remote Instruction - Robinson, Julie; Hammack, Rebekah (Innovations in Science Teacher Education, 2022)
We implemented a remote collaborative inquiry project with elementary preservice teachers who were enrolled in their science methods course during the 2020–2021 academic year. The courses were taught in one of three modalities: (1) fully online and asynchronous (graduate students seeking initial licensure), (2) fully online with synchronous and asynchronous components (undergraduate students), and (3) blended with face-to-face and asynchronous online components (undergraduate students). During the project, groups of two to four preservice teachers engaged remotely in collaborative, hands-on inquiry projects and documented their communication throughout the process. The remote collaborative inquiry projects were adapted from existing course assignments that had previously been used in face-to-face settings. We found that despite encountering some unexpected challenges with implementation, most participants recognized the value of group work for learning science. However, many preservice teachers, especially undergraduate students, focused on completing a quality end product rather than the learning that occurred throughout the process of collaboration and inquiry. It was also clear that many did not differentiate between collaborative and cooperative learning and often utilized a divide-and-conquer cooperative strategy. Future implementations of the project should intentionally provide opportunities for preservice teachers to discuss the differences between collaboration and cooperation and how these strategies impact learning in addition to the completion of a final product.